ALTERNATIVE DESIGN AND ECONOMIC FEASIBILITY OF AN EXPERIMENTAL WHR FOR INTAKE AIR CONDITIONING OF A LARGE INTERNAL COMBUSTION ENGINE - Paula, V. B.; Chun, A.; Miotto, B. M.; Cunha, C. C. M.; Santos, J. J. C. C. S. (Revista de Engenharia Térmica, 2020)
This work presents an alternative design for an experimental waste heat recovery thermal system to be coupled to a large turbocharged internal combustion engine for combustion air conditioning. The goal is to carry out a design of a new thermal system under restricted economic requirements for one of the generators set of Luiz Oscar Rodrigues de Melo Thermoelectric Power Plant. Thereby, a comparison with the original proposal from previous works is also developed in order to demonstrate the differences in terms of thermo-economic design parameters. The waste recovery thermal system produces sufficient chilled water through a single-effect absorption chiller, powered by hot water which is produced by recovering the exhaust gases residual heat to supply cooling applications on the combustion air. The results showed a significant reduction for the chiller capacity demand, from 550 to 185 RT, that would be enough to provide chilled water for 98.72% of the analyzed operation historical period. The economic feasibility indicators reveal the proposal for the alternative waste heat recovery system as the best financial option, presenting a lower investment cost (US$316,793.27 of savings) and a time for capital recovery of 2.14 years, 1.61 years shorter when compared with the initial WHR system.